Optimal tyre management for a high-performance race car. Issue 1 (2nd January 2022) - West, W. J.; Limebeer, D. J. N.
ABSTRACT: Optimal control is used to study the management of tyre performance for a Formula One car. Tyre friction is compromised by accumulated wear and operation outside the tyre design temperature window – inappropriate thermal operation accelerates tyre wear. In this study tyre wear is modelled as a function of the tyre surface temperature and the power dissipated at the road contact. The tyre's frictional performance is modelled as a function of temperature and accumulated wear. A previously developed thermodynamic model is modified by the addition of a state representing the tyres' carcass temperature. Optimal control calculations are used to optimise (multi-lap) performance by improving grip and extending the life of the tyres. In combination, tyre wear and friction control can be used to schedule tyre changes and minimise race times.